The Effect of Reading Strategy and Personality Traits in Improving The Students' Reading Comprehension Achievement - Astuti, Prihatin Puji (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This paper investigated the effect of reading strategy and personality traits in improving students’ reading comprehension achievement. This reseach was conducted at the grade 12 students of SMK Sasmita Jaya 2 Pamulang, Tangerang Selatan. The researcher administered  quantitative research under quassy esperimental research through pre test and post test. The two reading strategies named QAR (Question and Answer Relationship) reading strategy and KWL (Know Want know and Learn) reading strategy were andministrated to the students. The pre test and post test were applied in order to know the effect of the reading strategy toward the students’ reading comprehension achievement, meanwhile the  questioner of MBTI (Myers-Briggs Type Indicator) was administrated to  the students to know their types of personality whether they are extrovert and introvert. After analysing the data, it was found that there is significant improvement of the students reading comprehension achievement  after the strategy  being applied. However the result also showed that  there is no significant difference between QAR reading strategy and KWL raeding strategy in improving students reading comprehension achievement. Meanwhile from the calculation of SPSS, the result showed that there is no  significant interaction between   personality  toward  the students’  reading comprhension achievement.